Measuring Empathy in Pharmacy Students - Fjortoft, Nancy (American Journal of Pharmaceutical Education, 2011)
Objective. To validate the Jefferson Scale of Empathy-Health Profession Students version (JSE-HPS) in pharmacy students. Methods. The JSE-HPS (20 items), adapted from the original Jefferson Scale of Empathy for use among students in the healthcare professions, was completed by 187 first-year pharmacy students at Midwestern University Chicago College of Pharmacy. Results. Two factors, “perspective-taking” and “compassionate care,” emerged from factor analysis in this study, accounting for 31% and 8% of the variance, respectively. These factors are similar to the prominent ones reported in previous research involving physicians and medical students, supporting the construct validity of this instrument for pharmacy students. In the current study, mean JSE-HPS score was comparable to those reported for medical students, and consistent with previous findings with medical students and physicians. Women scored significantly higher than men. Conclusions. Findings support the construct validity and reliability of the JSE-HPS for measuring empathy in pharmacy students.